IMPROVING STUDENTS 'MATHEMATICAL COMMUNICATION SKILLS THROUGH THE RECIPROCAL TEACHING MODEL - Sardin Sardin (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2019)
The objective of this research was to find out the improvement of students’ mathematical communication ability through learning model of reciprocal teaching at class VII-B Of SMP Negeri 2 Bonegunu. This research was a classroom action research. The population in this research was all grade VII students of SMP Negeri 2 Bonegunu as many as 63 students and the sample was class VII-B students of SMP Negeri 2 Bonegunu whose number was 31 students. The instruments of this research were an observation sheet and a test of students’ mathematical communication ability. Based on the research outcome. It obtained the score of teacher’s activity was 88.24% and students’ activity was 70,58% which was implemented. At cycle II, the teacher’s acthivity which was implemented was 97,06% and students’ activity was 91,18%. The result of students’ mathematical communication ability indicated that there was not any student who got a score of ≥65. The test result at cycle I Indicated that students’ mathematical communication ability was 70,97% (22 students) got a score of ≥ 65 with the mean score was 70,84. The result of posttest at cycle II indicated that students whose score ≥ 65 were 26 students (88,87%) with the mean score were 77,87. Of those result, it was obtained the conclusion that students’ mathematical communication ability at class VII-B of SMP Negeri 2 Bonegunu could be improved by apllying the reciprocal teaching model.